Hubungan Literasi Fisik dengan Tingkat Aktivitas Fisik Siswa SMP - Dany Firman Lazuardi; Abdul Rachman Syam Tuasikal; Miftakhul Jannah (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
Physical activity among adolescents remains relatively low and tends to decrease with age. One factor associated with students’ physical activity behavior is physical literacy. This study aimed to analyze the relationship between physical literacy and physical activity levels among junior high school students. A quantitative approach with a cross-sectional design was applied involving 239 students from grades VII, VIII, and IX at SMP Hang Tuah 4 Surabaya. Data were obtained using the Adolescent Physical Literacy Questionnaire (APLQ) and the International Physical Activity Questionnaire (IPAQ). Data analysis involved descriptive statistics, Shapiro-Wilk normality test, Spearman correlation, and simple linear regression. The findings revealed a significant positive relationship between physical literacy and students’ physical activity levels (r = 0.323; p < 0.001). Physical literacy also showed a significant contribution to students’ physical activity (β = 0.217; p = 0.001) with a determination value of 4.7%. These findings indicate that physical literacy contributes to students’ engagement in physical activity and may support the development of physical education learning oriented toward active lifestyles. Keywords: Physical Activity, Physical Literacy, Adolescents, Junior High School Students